Integrating Behavioral and Social Science Research Into Microbicide Clinical Trials: Challenges and Opportunities. - Tolley, Elizabeth E.; Severy, Lawrence J. (American Journal of Public Health, 2006)
It has been argued that rigid thinking about the types and progression of research needed to evaluate health promotion interventions has stymied the process by which research is translated to action. This argument is particularly salient in the field of HIV/AIDS prevention. We examined microbicide research and identified challenges that obstruct the integration of clinical trial and behavioral and social science research, thereby reinforcing linear programs of research. We found that behavioral and social science research can both support microbicide clinical trial performance and anticipate the information most needed for a rapid and successful introduction of future microbicide products. (Am J Public Health. 2006; 96:79-83.)